Predicting hygienic food handling behaviour: Modelling the health action process approach - Mullan, Barbara; Wong, C.; O'Moore, K. (Emerald Group Publishing Limited, 2010)
Purpose – The purpose of the current paper is to investigate the determinants of hygienic food handling behaviour using the health action process approach (HAPA) and to examine if the volitional components of the model or the addition of past behaviour could explain additional variance in behaviour. Design/methodology/approach – A prospective four-week study investigating the predictive ability of HAPA variables and past behaviour was used. At time 1, 109 participants completed self-report questionnaires regarding their action self-efficacy, risk awareness, outcome expectancies and intentions to hygienically prepare food and past behaviour. At time 2, participants returned a follow-up questionnaire, which measured behaviour, planning, maintenance and recovery self efficacy. Structural equation modelling was used to compare three versions of the HAPA model. Findings – The first model showed that intention was a significant predictor of behaviour explaining 40 per cent of the variance and was the best fit. The second model, which included the volitional components of the HAPA model, did significantly increase the proportion of behaviour explained. The third model, which included past behaviour, increased the variance explained but was not a superior fit to the previous two models. Practical implications – The results of this study confirm that aspects of the HAPA may be useful in determining hygienic food handling behaviour. However, volitional variables do not appear to be important in this behaviour. The implications of this for future research and interventions are elucidated. Originality/value – The current study is one of the first to use the HAPA model to predict hygienic food handling behaviour.